PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII1 SMP NEGERI 1 TELUK KUANTAN - Putri, R.Iska Meili; Maimunah, Maimunah; Suhermi, Suhermi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research aims to improve student’s mathematics learning achievement through implementation of Contextual Teaching and Learning approach. This type of research is Classroom Action Research with two cycle. The research was conducted in class VIII1 SMPN 1 Teluk Kuantan at the first semester of the 2018/2019 academic year. The subject of this researchconsist of 32 students, there are 19 female students and 13 male students. The research instrument consists of learning materials (Sylabus, Lesson Plan, and Activity Sheets) and instruments for collecting data (Observation Sheets and Mathematical achievement test). Data analysis technique in this study are descriptive narrative analysis of qualitative data and descriptive statistics analysis ofquantitative data. Based on analysis of the observation sheet, the application of Contextual Teaching and Learning approach can improve the learning process as indicated by the increase in the activity of teacher and students in each cycle. Data obtained from mathematical achievement test result the percentage of students which ispass Minimum Mastery Crieria (MMC) increase from 37,5% to 59,4% at the first test and to 75% at the second test. This research concludes that the implementation of Contextual Teaching and Learning approach improved the learning process and the student’s mathematical achievement at class VIII1 SMPN 1 Teluk Kuantan in the first semester of the 2018/2019 academic year.Key Words : Mathematics Learning Achievement, Contextual Teaching and Learning approach, Classroom Action Research.